Dynamics, stability and bifurcation analysis of rotors in air ring bearings. (17th March 2022) - Zeise, Pascal; Schweizer, Bernhard
Abstract: Classical air foil bearings consist of a top foil, which is usually supported by a bump or beam foil structure. For this bearing type, the air gap is a function of the top foil deformation. Here, an alternative air bearing design – called air ring bearing – is investigated, which may be regarded as a straightforward and very obvious modification of the classical air bearing design. The basic idea is to insert a rigid ring between the shaft and the foil structure. The ring may therefore be considered to be elastically mounted in the housing by means of a bump or beam-type structure. Alternatively, a viscoelastic supporting structure (elastomer) may be used to connect the ring with the housing. Hence, the air film is separated by a rigid ring from the supporting structure. As a consequence, the bearing gap for the fluid film has rigid walls, which simplifies the numerical calculation significantly. In this manuscript, a detailed numerical analysis of rotor systems supported in air ring bearings is presented. The basic nonlinear dynamical effects occurring in such rotor systems are investigated with a particular focus on the stability and bifurcation behavior. Therefore, a detailed co-simulation model of the rotor/bearing system is used. Different possible bifurcation scenarios are described and explained with the help of run-up simulations. Rotor systems with air ring bearings exhibit a completely different vibration and stability behavior than rotors in classical air foil bearings. Diverse interesting nonlinear vibration phenomena, not known in connection with classical air foil bearings, are discussed in detail and physically explained in a clear manner.